Recent Trends and Future Direction for Data Analytics - Kumari, Aparna, 1984- (Hershey, PA : IGI Global, Engineering Science Reference (an imprint of IGI Global), 2024)
"Our journey as editors in compiling this book began with a vision to offer a holistic understanding of data analytics, covering foundational principles to advanced applications. Each chapter is carefully crafted to provide a blend of theoretical insights and practical case studies, ensuring readers understand the subject matter comprehensively. The book's structure facilitates learning progression, starting with fundamental concepts like data preparation and exploratory data analysis and progressing to advanced topics such as predictive modelling and clustering. Real-world case studies from diverse industries offer valuable insights into how data analytics addresses complex challenges and drives innovation"--
Dr. Fakhitah Binti Ridzuan
Includes bibliographical references and index
Keywords: Quantitative research; Quantitative research -- Data processing; Big data